2018
DOI: 10.1016/j.cub.2017.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Abolishment of Spontaneous Flight Turns in Visually Responsive Drosophila

Abstract: Animals react rapidly to external stimuli, such as an approaching predator, but in other circumstances, they seem to act spontaneously, without any obvious external trigger. How do the neural processes mediating the execution of reflexive and spontaneous actions differ? We studied this question in tethered, flying Drosophila. We found that silencing a large but genetically defined set of non-motor neurons virtually eliminates spontaneous flight turns while preserving the tethered flies' ability to perform two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 59 publications
(89 reference statements)
1
22
0
Order By: Relevance
“…Across stimulus intensities and spatial configurations, we found that turn dynamics reflected both mechanosensory and visual input; antennal stabilization experiments argue that these signals are integrated within the brain. Although integration of both modalities was visible in nearly every stimulus configuration we tested, unexpected turns also occurred in many of our experiments, suggesting that the integrative process on which we have focused must coexist with mechanisms to generate stochastic turns [7,29,30]. …”
Section: Discussionmentioning
confidence: 96%
“…Across stimulus intensities and spatial configurations, we found that turn dynamics reflected both mechanosensory and visual input; antennal stabilization experiments argue that these signals are integrated within the brain. Although integration of both modalities was visible in nearly every stimulus configuration we tested, unexpected turns also occurred in many of our experiments, suggesting that the integrative process on which we have focused must coexist with mechanisms to generate stochastic turns [7,29,30]. …”
Section: Discussionmentioning
confidence: 96%
“…Mitochondria are vital in regulating cellular adaption to stressors, including impaired biogenesis, mitochondrial DNA (mtDNA) damage, ageing, nutrient restriction and aberrant imbalances between fission and fusion events. If left unchecked, these processes can cause damage to nucleic acids, lipids and proteins through ROS, resulting in sustained oxidative stress [ 16 , 17 ]. Oxidative stress modulates mitochondrial dynamics through posttranscriptional modifications, including ubiquitination [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The short bar saccade rate was higher than previously reported spontaneous saccade rates in the magnetic tether (∼0.4 saccades s −1 ) (Bender and Dickinson, 2006;Mongeau and Frye, 2017), suggesting that the short bar stimulus elicited visually guided saccades. However, we expect that some saccades we measured were spontaneous, triggered by endogenous processes (Ferris et al, 2018;Schnell et al, 2017). Nevertheless, there was a significant association between the stimulus type and saccade valence (χ 2 test, P<0.001, d.f.=1, n=2833 saccades).…”
Section: Resultsmentioning
confidence: 82%